2021
DOI: 10.1016/j.jmgm.2020.107778
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the intrinsic dynamics of SARS-CoV-2, SARS-CoV and MERS-CoV spike glycoprotein through normal mode analysis using anisotropic network model

Abstract: COVID-19 caused by SARS-CoV-2 have become a global pandemic with serious rate of fatalities. SARS-CoV and MERS-CoV have also caused serious outbreak previously but the intensity was much lower than the ongoing SARS-CoV-2. The main infectivity factor of all the three viruses is the spike glycoprotein. In this study we have examined the intrinsic dynamics of the prefusion, lying state of trimeric S protein of these viruses through Normal Mode Analysis using Anisotropic Network Model. The dynamic modes of the S p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 30 publications
0
23
0
Order By: Relevance
“…[30] and Xiong et al . [34] or taken into consideration in several other structural studies [20-24]. As such, we employ the two-state model shown in Figure 2, with one state representing all three RBD domains closed and the second state representing one RBD open.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[30] and Xiong et al . [34] or taken into consideration in several other structural studies [20-24]. As such, we employ the two-state model shown in Figure 2, with one state representing all three RBD domains closed and the second state representing one RBD open.…”
Section: Resultsmentioning
confidence: 99%
“…4, unclear if any additional conformational states other than those with either all three RBD domains in the closed state or only one RBD open state are biologically relevant. Specifically, Yurkovetskiy et al [44] observed an occupancy for states with two or three RBD domains in the open conformation, but these were not observed by Gobeil et al [30] and Xiong et al [34] or taken into consideration in several other structural studies [20][21][22][23][24]. As such, we employ the two-state model shown in Figure 2 [30] and Xiong et al [34].…”
Section: Conformational State Occupanciesmentioning
confidence: 97%
See 1 more Smart Citation
“…As we note in Section 1 , we have known for a while that proteins are dynamic molecules that switch between different structures under physiological conditions. There has never perhaps been a better time when protein dynamics has been front and center in the public eye; we point here to a growing number of studies reported broadly in media showing the equilibrium motions of the receptor binding domain, the S1 subunit, of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) spike glycoprotein between a closed to a partially-open structure being key to its ability to bind to the human Angiotensin-converting enzyme 2 (ACE2) receptor and so mediate viral entry in human host cells [ 33 , 34 , 35 ]. Finding the structures that a protein accesses to regulate interactions with molecular partners in the cell is an important problem.…”
Section: Discussionmentioning
confidence: 99%
“…ACE2 receptors are present in almost all human organs as well as in the wide variety of cells including smooth muscle cells and endothelial cells of the lungs, stomach cells, colon, small intestine cells, liver cells, kidney cells, and also brain ( Shereen et al, 2020 ; Zhang et al, 2020a ). Recent findings revealed key structural differences and the intrinsic sequence of the RBDs of both of the SARS-CoV and SARS-CoV-2 ( Majumder et al, 2020 ). The precise understanding of the interaction of the SARS-CoV-2 virus with ACE2 human cells receptors is now revealed after detailed structural analysis RBD–ACE2 complex using X-ray crystallographic examinations ( Lan et al, 2020 ).…”
Section: Biological Characteristics Of the Sars-cov-2mentioning
confidence: 99%